Design and Evaluation of a Blockchain-Based Traceability Model for Organic Rice Supply Chain - Rohmat Taufiq; Harco Leslie Hendric Spits Warnars; Haryono Soeparno; Tanty Oktavia (Ital Publication, 2026)
This study aims to design and evaluate a blockchain-based traceability model and prototype for the traceability of organic rice supply chains in Banten Province, Indonesia. The main problem identified is the absence of a digital system that can transparently trace the origin of organic rice, which has reduced consumer trust in product authenticity. This research adopts the Design Science Research Methodology (DSRM) to develop a traceability model and prototype capable of recording all supply chain activities from farmers to end consumers. The prototype was validated using the ISO/IEC 25010 standard with supply chain actors and further validated with end consumers. Validation results from supply chain actors indicate strong performance across maintainability (4.91), functional suitability (4.29), security (4.11), performance efficiency (3.98), compatibility (3.89), usability (3.85), reliability (3.80), flexibility (3.93), and safety (3.77). Meanwhile, validation with end consumers yielded an average score of 4.22 on a 1–5 Likert scale. These findings indicate that the system meets key quality attributes—particularly functionality, reliability, security, and maintainability—at a very good level. In conclusion, implementing blockchain technology for organic rice supply chain traceability can enhance transparency, improve data security, and strengthen consumer trust in organic rice products.